2010
DOI: 10.1158/1078-0432.ccr-09-2175
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Renal Cell Carcinoma Treated with Sunitinib: Early Evaluation of Treatment Response Using Dynamic Contrast-Enhanced Ultrasonography

Abstract: Purpose: To determine the utility of dynamic contrast-enhanced ultrasonography (DCE-US) as a prognostic tool for metastatic renal cell carcinoma patients receiving sunitinib and to identify DCE-US parameters that correlate with early treatment response.Experimental Design: Thirty-eight patients received 50 mg/d sunitinib on schedule 4/2 (4 weeks on followed by 2 weeks off treatment). After two cycles, response evaluation criteria in solid tumors were used to classify patients as responders or nonresponders. DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 17 publications
3
116
0
2
Order By: Relevance
“…This is a major result considering the previous findings reported by Lassau et al [22,56,57] in different types of tumors such as GIST or RCC: among the seven semi-quantitative perfusion parameters evaluated, the two parameters which always correlated with the RECIST response and overall survival were the AUC and the AUWO. These two complementary observations highlight the reliability of such parameters in assessing anti-angiogenic treatments: AUC and AUWO are associated to a good correlation to RE-CIST response as well as to low intra-operator variability values.…”
Section: Anti-angiogenesis Therapies and Dce-us Imagingsupporting
confidence: 73%
See 1 more Smart Citation
“…This is a major result considering the previous findings reported by Lassau et al [22,56,57] in different types of tumors such as GIST or RCC: among the seven semi-quantitative perfusion parameters evaluated, the two parameters which always correlated with the RECIST response and overall survival were the AUC and the AUWO. These two complementary observations highlight the reliability of such parameters in assessing anti-angiogenic treatments: AUC and AUWO are associated to a good correlation to RE-CIST response as well as to low intra-operator variability values.…”
Section: Anti-angiogenesis Therapies and Dce-us Imagingsupporting
confidence: 73%
“…The second experiment was performed by injecting five times a 0.05 mL bolus of SonoVue ® . This volume involved a ratio routinely used for clinical exams (4.8 mL of SonoVue ® for 5 L of blood) and particularly in four studies performed at the Gustave Roussy Institute (IGR), involving 117 patients and 823 DCE-US exams [21,22] as well as a national project supported by the "Institut National du Cancer" (French National Cancer Institute) [23] . The last experiment involved five 0.08 mL bolus injections of SonoVue ® .…”
Section: Time-intensity Methodsmentioning
confidence: 99%
“…Time to peak intensity and area under the curve, which correlate with blood flow and blood volume, can be quantified. In patients with mRCC treated with sunitinib, Laussau et al [30] showed that DCE ultrasonography parameters at baseline and on day 15 were significantly different between responders and non-responders. DCE ultrasonography does have a major drawback as the discipline cannot evaluate lesions localized to the lung, the most common site of metastases in RCC.…”
Section: Dce Ultrasonographymentioning
confidence: 99%
“…Dynamic contrast enhanced ultrasound (DCE-US) refers to quantitative time intensity curve (TIC) analysis [11][12][13] using either bolus injection of microbubbles [13][14][15][16] or intravenous infusion with disruption-replenishment technique [17] which are used for treatment response evaluation in oncology [18] and for activity assessment in inflammation of the bowel wall in inflammatory bowel disease [19][20][21][22]. 3D CEUS refers to image acquisition of data volumes.…”
Section: An Introduction To Terminologymentioning
confidence: 99%